Effect of high pressure homogenization combined with juice ratio on water-soluble pectin characteristics, functional properties and bioactive compounds in mixed juices. (March 2020) - Wellala, Chandi Kanchana Deepali; Bi, Jinfeng; Liu, Xuan; Liu, Jianing; Lyu, Jian; Zhou, Mo; Marszałek, Krystian; Trych, Urszula
Abstract: The effect of high pressure homogenization (HPH) processing combined with juice ratio on overall quality attributes of carrot, apple and peach mixed juices were investigated. Relationships of functional properties with physicochemical and particle characteristics were analyzed, while relevance of bioactive compounds and antioxidant activity (AOA) with water-soluble pectin (WSP) characteristics were also investigated. As the results indicated, juice ratio of individual juices affected physicochemical attributes, and composition of WSP and bioactive compounds in mixed juices. HPH processing decreased particle size and altered WSP characteristics. Moreover, HPH influenced functional properties of mixed juices, including cloud stability and rheological behavior, which were correlated with physicochemical and particle characteristics. Polyphenols contributed more for AOA. HPH processing enhanced polyphenol content, which showed significant positive correlations with content and degree of methylesterification of WSP. Thus, AOA was relevance to both polyphenol and WSP contents, implying that interactions between polyphenol and pectin could enhance AOA. Industrial relevance: When physically and chemically different plant matrixes are mixed together to produce mixed juices, sedimentation and instability of bioactive compounds, including carotenoids and polyphenols could occur, which are identified as key challenges in the beverage industry. This research provides guidance for formulating mixed juices and introduces the potential application of high pressure homogenization for enhancing functional properties and stability of bioactive components.